LEGALITAS PEMERIKSAAN SIDANG PERKARA PIDANA MELALUI MEDIA TELECONFERENCE DI MASA PANDEMI COVID-19 - Cahyadi, Faisal; Utami, Hilda Restu (Veritas et Justitia, 2021)
AbstractThe focus of this research is to identify regulations governing the implementation of criminal case trials using teleconference media in Indonesia and to analyze the legality of these trials during the COVID-19 pandemic. This research is a normative legal research. Legal materials are obtained through literature study and interviews with legal practitioners, then processed qualitatively. Based on the results, the author obtained two conclusions. First, regulation of criminal case trials using teleconference media in Indonesia has been regulating in several laws in Indonesia. Second, the implementation of the trial during the COVID-19 pandemic, which required the defendant to remain in prison, was contrary to the principle of the defendant's presence at trial as regulated by the Criminal Procedure Code. Besides, the legal-based in the form of a circular cannot override the Criminal Procedure Code. Meanwhile, the legal umbrella in the form of an agreement is not appropriate considering its dimensions are private and only bind the parties. Keywords:criminal trials, teleconference, the COVID-19 pandemic AbstrakFokus pembahasan penelitian ini adalah mengidentifikasi peraturan perundang-undangan yang mengatur pelaksanaan sidang teleconference di Indonesia dan menganalisis legalitas persidangan perkara pidana yang memanfaatkan media teleconference di masa pandemi COVID-19. Penelitian ini merupakan penelitian hukum normatif. Bahan hukum diperoleh melalui studi kepustakaan dan wawancara dengan praktisi hukum yang kemudian diolah secara kualitatif. Berdasarkan hasil penelitian, Penulis memperoleh dua kesimpulan. Pertama, pemeriksaan sidang perkara pidana melalui media teleconference di Indonesia sudah diatur dalam beberapa peraturan perundang-undangan di Indonesia. Kedua, pelaksanaan persidangan tersebut di masa pandemi COVID-19 yang mengharuskan terdakwa tetap berada di Rutan/Lapas bertentangan dengan asas kehadiran terdakwa di persidangan sebagaimana diatur oleh KUHAP. Selain itu, payung hukum berupa surat edaran bukan merupakan peraturan perundang-undangan sehingga tidak dapat mengenyampingkan KUHAP. Sedangkan, payung hukum berupa perjanjian kerja sama tidaklah tepat mengingat dimensinya yang bersifat privat dan hanya mengikat para pihak. Kata Kunci:persidangan pidana, teleconference, pandemi COVID-19